PERILAKU PENGHUNI RUMAH DOME DI PRAMBANAN SLEMAN ADAPTASI DAN ADJUSTMENT DI SETING BARU , : - Rusydi, Mohammad (Institut Seni Indonesia Yogyakarta, 2008)
Dome houses in the village of Sengir, Sumberharjo, Prambanan, Sleman, Yogyakartais aids from the World Assossiation of Non-Government Organization cooperated with theUnited States for the World Dome for victims of the earthquake which occurred in May 2006.Occupants of the house that started fromtheir house before the earthquake and then occupyingthe dome houses, and will adjust themselves (coping) with a new place. This adjustmentresulted in occupant behavior change (adaptation) or the population will change the housingenvironment (adjustment). The research problem is how the behavior of the dome dweller usedthe facility to accommodate activities that occur therein. The purpose of this study was to identifythe occupant behavior in the new setting. Occupant behavior was investigated by interview andobservation followed by mapping the behavior (behavioral mapping). Inductive analysis ofoccupant behavior and solution strategies in new settings by using categorization, descriptionsand explanations. Outline the research findings can be stated as follows: a) Strategy indetermining the behavior of new solutions (behaviors) that change the behavior or maintain thebehavior, b) Strategies for the dome houses a solution (physical) that makes the settings in thedome house or make new settings in the outer dome room, and c) Perception of the populationexperiencing a change after the physical and behavioral strategies.Keywords: dome house, behavior, adaptation, adjustment